Theory of knowledge structures and processes - Burgin, M. S. (Mark Semenovich) (World Scientific series in information studies, 2017)
This book aims to synthesize different directions in knowledge studies into a unified theory of knowledge and knowledge processes. It explicates important relations between knowledge and information. It provides the readers with understanding of the essence and structure of knowledge, explicating operations and process that are based on knowledge and vital for society.